Government Actors’ Meaning Making of Digital Governance Transformation in Contemporary Public Policy - Didik Sasono Setyadi; Aris Nikmatullah (PT FORMOSA CENDEKIA GLOBAL, 2026)
Digital governance transformation in public policy is not only driven by technological adoption but also shaped by how government actors interpret and construct its meaning. This article analyzes how government actors make sense of digital governance transformation and how these interpretations influence policy and bureaucratic change. The study adopts a qualitative approach based on systematic literature review of academic sources and policy documents on digital governance. The findings reveal three dominant interpretations among government actors: digitalization as an administrative efficiency tool, as a mechanism for transparency and accountability, and as a structural reform agenda for bureaucratic transformation. These differences are shaped by institutional capacity, digital literacy, and political context. The study highlights that the success of digital governance transformation depends not only on technological infrastructure but also on shared meaning construction among government actors.